Orientation to the Future of Gifted Primary Schoolchildren: Near and Far Goals - Kulagina I.Y.; Shumakova N.B. (Психолого-педагогические исследования, 2021)
The article presents research data on the attitude of gifted children aged 9-10 years to different ages, their ideas about the future, setting short-and long-term goals. There is a great creative potential of giftedness, but how much it will be realized when reaching maturity depends not only on cognitive sphere, but also on the characteristics of the personality. The psychological literature contains contradictory information about the personal characteristics of gifted children; there is very little data on such aspect of personal development as orientation to the future, which determines the relevance and novelty of the study. The study involved 96 children with IQ≥115, enrolled in grades 3 and 4 of the gymnasium for gifted children, and 104 children enrolled in grades 3 and 4 of the secondary school under the traditional program (Moscow). We used the modified method of B. Zazzo “Golden age”, the projective method “Unfinished sentences” and the method of M.V. Matyukhina, which allows us to determine educational motivation in primary school age. It is shown that the majority of primary school children prefer youth as the age period of maximum opportunities. Gifted children are less likely than their peers with normative intellectual development to set short-range goals of good and excellent studies, self-improvement in activities that require physical effort, and more goals related to filling the lack of emotional support. The area of long-range goals related to youth is wider for younger students. Gifted children have a more pronounced orientation to high material security and freedom in its various manifestations, to a lesser extent – to the traditional construction of life (work, family, children).